2008
DOI: 10.1007/s00420-008-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial working conditions and self-reported health in a representative sample of wage-earners: a test of the different hypotheses of the Demand–Control–Support–Model

Abstract: The strong effects of job demands, support, job strain and active learning are suggesting that a policy aimed at improving psychosocial working conditions should focus on a bearable level of job demands and the quality of social relationships at work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
5
31
0
3
Order By: Relevance
“…Our results are consistent with the review of 14 epidemiological studies that found the associations between the DCS model and depression were strongest and most consistent with respect to demand and work social support, while the results of control were contradictory (Netterstrom et al 2008;Vanroelen et al 2009). On the other hand, our results are slightly diVerent from the Wndings that low control, high demand and low work social support are risk factors for depression in other occupations (Plaisier and De Bruijn 2007;Mausner and Eaton 2000;Cropley et al 1999).…”
Section: Job Stress Models and Depressive Disorders In Microelectronisupporting
confidence: 94%
“…Our results are consistent with the review of 14 epidemiological studies that found the associations between the DCS model and depression were strongest and most consistent with respect to demand and work social support, while the results of control were contradictory (Netterstrom et al 2008;Vanroelen et al 2009). On the other hand, our results are slightly diVerent from the Wndings that low control, high demand and low work social support are risk factors for depression in other occupations (Plaisier and De Bruijn 2007;Mausner and Eaton 2000;Cropley et al 1999).…”
Section: Job Stress Models and Depressive Disorders In Microelectronisupporting
confidence: 94%
“…Lien et al reported that compared with the general Taiwanese adult population, patients with symptomatic gallstone disease had significantly poorer performance on all eight SF-36 subscales (P \ 0.001) [44]. Vanroelen et al reported that high job demands were related to a higher prevalence of persistent fatigue, musculoskeletal complaints and emotional problems and were the strongest indicator for each of the adverse health outcomes, such as persistent fatigue, musculoskeletal problems and emotional wellbeing [45].…”
Section: Quality Of Lifementioning
confidence: 99%
“…Low support at work has long been found to affect levels of anxiety, emotional exhaustion, job tension and job satisfaction (e.g. de Lange et al, 2004;Vanroelen et al, 2009). In a Finnish study of 383 PhD students, Stubb, Pyhältö and…”
Section: Work Contextmentioning
confidence: 99%